Mitigating Salinity Stress in Pea Plants with Titanium Oxide Nanoparticles - Ekaterina Yotsova; Martin Stefanov; Georgi Rashkov; Anelia Dobrikova; Emilia Apostolova (International Journal of Plant Biology)
Changes in the environment have a significant impact on photosynthetic efficiency, which in turn influences plant growth and yield. Consequently, there is a greater focus on methods to enhance photosynthetic efficiency with the goal of raising plant productivity. In this study, the effects of titanium oxide nanoparticles (TiO2 NPs) on pea plants (Pisum sativum L.) subjected to moderate salt stress by the addition of 100 mM NaCl to the nutrient solution were investigated. Two concentrations of NPs (50 mg/L and 100 mg/L) were applied through foliar spray on pea leaves. Data showed that NPs prevent salt-induced membrane damage, growth inhibition, and the increase in hydrogen peroxide and lipid peroxidation. An analysis of the chlorophyll fluorescence curves revealed that TiO2 NPs decreased the effects of NaCl on the reduction in the open photosystem II centers (corresponding with qp) and their efficiency (Φexc), as well as the activity of the oxygen-evolving complex (Fv/Fo). The co-treatment with TiO2 NPs and NaCl also improved the photochemical energy conversion of photosystem II (ΦPSII), alleviated the interaction of QA− with plastoquinone, and enhanced electron transport activity and the rate of photosynthesis, compared to the plants treated with NaCl only. Additionally, NPs application under salt stress stimulated cyclic electron transport around photosystem I, thus protecting its photochemical activity. These protective effects of NPs were more pronounced at a concentration of 100 mg/L.